UJI BEDA PENGARUH ARUS KAS OPERASI DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA PERUSAHAAN FOOD AND BAVERAGE DI BEI DAN BURSA EFEK FILIPINA - Anida Zuhrotul Laili; Sugeng Hariadi (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to analyze and obtain empirical evidence of the difference in the influence of operating cash flow and debt levels on earnings persistence in 2017-2019. The dependent variable of this study is earnings persistence, while the independent variable of this study consists of operating cash flow and debt levels. The population of this study is the food and beverage sub-sector manufacturing companies in the Indonesia Stock Exchange and the Philippines Stock Exchange. The sample selection was done by using purposive sampling technique and resulted 81 samples. The data analysis technique in this research is using descriptive statistical analysis, classical assumption test and hypothesis The classical assumption test includes normality test, multicollinearity test, heteroscedicity test and autocorrelation test. While the hypothesis test includes multiple linear regression analysis, partial test (t test) and difference test. The results of the hypothesis test show that the operating cash flow of companies on the IDX has a significant effect on earnings persistence, while the level of debt has no significant effect on earnings persistence. Companies in the Philippine Stock Exchange show that operating cash flow and debt levels have no significant effect on earnings persistence. Operating cash flow and debt levels show a negative effect on earnings persistence. In addition, the different test shows that there is a difference in the magnitude of the influence of operating cash flow and debt levels on earnings persistence in companies on the IDX and the Philippine Stock Exchange.